Kegagalan Fungsi Safety Valve LP STEAM DRUM HRSG 1.1 Muara Karang - Sahlan Sahlan; Irvan Buchari S. Taman; Rian Fauzi Ashidiq (Sekolah Tinggi Teknik - PLN, 2015)
PJB UP Muara Karang there are companies producing electrical energy, and use the HRSG (Heat Recovery Steam Generator) as supporting the production process. HRSG operating has the potential danger of explosion. Peroperasi HRSG so safely and reliably, it is one of the tools used is a safety valve. The main objective is the safety valve to ensure personal and equipment operation are protected from excess pressure conditions (over pressure). Safety valve designed to prevent accidents by removing excess pressure that occurs during the interruption process or system failure. Seat is part of the valve stable / dwell in safety valve. Disc are no moving parts, serving as a flow controller. Disc will move upwards so as to provide more space so that fluid can flow, move down when closing and pressing the seat tightly. When the spindle, where the disc is attached, is not working properly, or jammed, it can be said safety valve is damaged or malfunctioning. From the data obtained, it was found that the corrosion is the main cause of the safety valve is malfunctioning. Causes of corrosion can be due to factors metallurgy of the material itself or from the surrounding environment. But the condition of the corrosion can be minimized by carrying out routine maintenance in accordance with the standards of care of the safety valve.